Civilizar os sertões, consolidar o estado: a colônia militar do Jataí e os aldeamentos indígenas no Tibagi (1845-1897) - Bezerra, Jessika de Aquino [UNIFESP] (2015)
The purpose of our research is to analyze the creation of the Military Colony of Jataí and of the Indigenous Villages in the valley of the Tibagi River, in the north of the province of Parana, in the nineteenth century. That region was little known until then and inhabited by indigenous groups, and has suffered, after 1855, a process of expansion their boundaries with the start of the settlement on the area. Our timeframe cover the period from 1845 to 1897, in order to include since the first voyages of exploration undertaken by the entrepreneur João da Silva Machado to the region, until the moment of emancipation of the MC of Jataí. The creation of military colonies was part of an Imperial policy, made official in 1850, and aimed to establish order and control over the population considered dangerous: indians, runaway slaves and criminals. At that time, was also imminent the concern to consolidate the boundaries of national territory for constitute a sovereign country. In that sense, more than twenty of these enterprises (Military Colonies) have been established near borders with other countries or in the middle of the woods, in order to protect the communications through rivers and land. Only in the province of Parana were installed three military colonies (The MC of Jataí has been the first). Therefore, our research does not address only to regional history, but, above all, rescues a time of political and economic transformations in the Empire of Brazil, which were intended to enable the consolidation of the national State.